Intense field induced excitation and ionization of an atom confined in a dense quantum plasma. (11th August 2015) - Lumb, Shalini; Lumb, Sonia; Munjal, D; Prasad, V
Abstract: Exponential cosine screened Coulomb potential (ECSCP) has been widely used in various branches of physics e.g., solid-state physics, nuclear physics and plasma physics. The atomic photoionization processes under plasma shielding can serve as an efficient tool for study of plasma properties in various environments ranging from nano-scale devices to astrophysical objects. In the present study, ECSCP has been used to characterize a dense quantum plasma and its effect on the spectrum of an atom encaged in a spherical box has been investigated. The work has further been extended to study the response of such a system to a periodic laser field. Photoexcitation and ionization probabilities of the system have been studied as a function of applied laser field parameters using the non-perturbative Floquet technique. As the Floquet method requires exact energy values and oscillator strengths, the spectrum of confined system has been calculated using Bernstein-polynomial method. The variation of energy spectrum and oscillator strengths with screening as well as confinement parameters has also been explored.